PENGELOLAAN AKTIVITAS EKONOMI DI JALUR PEDESTRIAN DI KAWASAN PERTOKOAN SEKITAR MALL PEKANBARU DI JALAN SUDIRMAN KOTA PEKANBARU - Razak Priatama; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was held in Sudirman Road, Pekanbaru. The purpose of this research is to know the activity of economic actors in the shopping lane around Mall Pekanbaru. The topic of focus of this research is the adherence of users in economic activity to the management of pedestrian on the pedestrian shopping lane around Mall Pekanbaru. The author uses quantitative methods and uses sampling techniques for data instruments are observations, polls and documentation. Research finds that there are four (4) types of economic actors around the pedestrian Mall Pekanbaru. Research finds there are 46% of street vendors as economic actors, in addition there are 6.0% of hawkers as economic actors. There are also 14% of beverage merchants as economic actors. In addition there are 14% soles of shoes or shoe craftsmen as economic actors and there are 10% of people who parked as economic actors. Research also finds economic activity in the Pedestrian area (sidewalk) is as follows: trade, trade activity around the Pedestrian area (sidewalk) Mall Pekanbaru has been underway since the Mall Pekanbaru opened. 86% of respondents who did not get permission to open an economic business in the Pedestrian area (sidewalk) Mall Pekanbaru. There are 14% of respondents who get permission. Parking, from the information of the recap of the research questionnaire which is filled by the economic actors who open the parking lot is known not to ask permission to the authorities. The level of compliance of economic actors to the management found is as follows: Oknum Satpol PP (during observation), confirming that they have been doing socialization related to the sale of sales, actually from late afternoon at 16.00 Wib until Evenings. But the business actors do not heed the appeal of the Sehut and still open a business break from the morning in the pedestrian area. 47% of respondents did not comply with the City Transportation Service, Pekabaru, to get the sales order as directed. 32% of respondents had experienced security issues.   Keywords: Pedestrian, economic actors, economic activity